Pemahaman Situasi Anak yang Berkonflik dengan Hukum pada Lembaga Pemasyarakatan Orang Dewasa: Suatu Kajian Literatur. (Jurnal Ilmu Kesejahteraan Sosial, 2018)
Based on data of the Prison Database System, on November 2013, the number of prisoners is 5730, with detail of 2233 were detained (with details of 2168 as boys and the rest were girls) and 3497 child delinquent (with details of 3428 boys and girls). The increase in cases of child delinquent is not balanced with the increase in the number of prisons and special detention for children. The number of special detention for Children in Indonesia is only 17 units out of 33 provinces. From 17 special detention for Children in Indonesia, there are only 8 units of special detention for Children that function specifically to handle children or the contents for children. While the other 9 correctional institutions that should be special for children, also functioned to accommodate adult prisoners. From total 33 provinces in Indonesia, there are 16 provinces that do not have a special prison for children. Thus, children facing the law will be placed in prisons and adult prisons. Seeing this situation needs attention from all parties (especially Government and Society) in handling this situation